Illusion-related brain activations: a new virtual reality mirror box system for use during functional magnetic resonance imaging - Diers, Martin; Flor, Herta (Brain research, 2015)
Extended viewing of movements of one’s intact limb in a mirror as well as motor imagery have been shown to decrease pain in persons with phantom limb pain or complex regional pain syndrome and to increase the movement ability in hemiparesis following stroke. In addition, mirrored movements differentially activate sensorimotor cortex in amputees with and without phantom limb pain. However, using a so-called mirror box has technical limitations, some of which can be overcome by virtual reality applications. We developed a virtual reality mirror box application and evaluated its comparability to a classical mirror box setup. We applied both paradigms to 20 healthy controls and analyzed vividness and authenticity of the illusion as well as brain activation patterns. In both conditions, subjects reported similar intensities for the sensation that movements of the virtual left hand felt as if they were executed by their own left hand. We found activation in the primary sensorimotor cortex contralateral to the actual movement, with stronger activation for the virtual reality ‘mirror box’ compared to the classical mirror box condition, as well as activation in the primary sensorimotor cortex contralateral to the mirrored/virtual movement. We conclude that a virtual reality application of the mirror box is viable and that it might be useful for future research.
Gesehen am 30.06.2017